A hydrogel and foam skeleton material composite interface evaporator and a preparation method thereof
Patent Information
- Application Number
- CN202510825274.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-19
AI Technical Summary
然而,现有技术难以同时兼顾界面蒸发器的隔热、输水、自浮、耐盐等方面的性能;比如具有良好输水性能的泡沫材料,其隔热性能较差,同时难以保证实际应用场景下的自浮效果;纳米级多孔结构具有优异的输水效果,但其制备过程中难以控制多孔结构的迂曲度,迂曲度越高,输水速率越低,并且越容易发生盐颗粒结晶堵塞问题,无法保证长期稳定性;一些聚合物材料具有优异的光热效应,但易滋生微生物,不仅会降低蒸发速率,还会降低水质;这些都会降低界面蒸发器的性能和使用寿命
(1)本发明所述泡沫骨架光热转化层具有多种无机光热转化材料,能够拓宽太阳光谱吸收范围,增强光吸收和光热转化性能,进而提高光热转换化温度,此外泡沫骨架光热层具有微米级多孔结构,有助于其利用自身毛细作用进行充分的水分扩散和传递,同时使光热层产生的蒸汽容易通过孔隙向外扩散,从而提高界面蒸发器的蒸发速率。
Smart Images

Figure HDA0005457883910000011 
Figure HDA0005457883910000012 
Figure HDA0005457883910000013
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photothermal interface evaporation technology, specifically relating to a composite interface evaporator of hydrogel and foam skeleton materials and its preparation method. Background Technology
[0002] In recent years, researchers have proposed using photothermal interface evaporation technology to localize the heat of photothermal conversion materials at the air-water interface. This approach can increase the temperature of the photothermal interface while avoiding the significant heat loss caused by bottom heating and volume heating, thereby improving the evaporation rate of the interface evaporator. Therefore, photothermal interface evaporators are an environmentally friendly, efficient, and clean method for seawater desalination.
[0003] Currently, existing technologies utilize semiconductors, plasma metals, carbon-based materials, and polymer materials as photothermal conversion materials. To ensure the interfacial evaporator floats on the water surface, lightweight foam is often used to achieve heat insulation and self-floating effects, thereby achieving thermal localization. For example, Chinese patent CN117585750A discloses a method for preparing a duplex photothermal interfacial evaporator, which consists of a carbon nanotube deposition layer for upper light absorption and an attapulgite composite hydrogel layer for lower water transport. Homogeneous nonwoven fabrics of different thicknesses are used as the three-dimensional network support for the carbon nanotube deposition and attapulgite hydrogel, with a strength of 1000 W / m. 2 The evaporation rate under light intensity reaches 2.92 kg / m³. 2 However, existing technologies struggle to simultaneously achieve optimal performance in interfacial evaporators, including heat insulation, water delivery, self-floating, and salt resistance. For instance, foam materials with excellent water delivery properties often exhibit poor heat insulation and are difficult to guarantee self-floating performance in practical applications. Nanoscale porous structures offer superior water delivery, but controlling the tortuosity of the porous structure during preparation is challenging. Higher tortuosity leads to lower water delivery rates and increases the likelihood of salt particle crystallization and blockage, compromising long-term stability. Some polymer materials possess excellent photothermal effects but are prone to microbial growth, which not only reduces evaporation rates but also degrades water quality. All of these factors contribute to reduced performance and lifespan of interfacial evaporators.
[0004] Despite the progress made in solar thermal conversion materials and interfacial evaporation structures, considering the actual application scenarios of solar thermal interfacial evaporators, in order to improve the evaporation rate and stability of interfacial evaporators, it is necessary to take into account the performance of heat insulation, water conveyance, self-floating, salt resistance, etc., and maximize the water production rate through multi-faceted balance. Summary of the Invention
[0005] The purpose of this invention is to provide a hydrogel and foam skeleton material composite interface evaporator and its preparation method, so as to solve the problems mentioned in the background art, take into account the requirements of heat insulation, water supply and self-floating, and improve the salt resistance of the interface evaporator while increasing the evaporation rate.
[0006] This invention provides the following technical solution: A composite interface evaporator of hydrogel and foam skeleton material includes two parts: a foam skeleton photothermal conversion layer and a water supply insulation layer. The water supply insulation layer is composed of hydrogel and closed-cell foam. The closed-cell foam reduces the heat loss from the photothermal conversion layer to the water body and achieves the self-floating effect of the composite interface evaporator. The closed-cell foam has millimeter-level vertical channels arranged in an array. Its upper and lower surfaces and the inner surface of the channels have hydrogel structures to achieve surface hydrophilic modification, forming a composite water supply insulation layer of hydrogel and closed-cell foam. Water is continuously transported from bottom to top through the constructed millimeter-level arrayed capillary water transport channels.
[0007] The foam skeleton photothermal conversion layer of the present invention uses metal oxide semiconductor as the substrate and has a nanostructure containing silver and silicon on the surface. By combining multiple inorganic photothermal materials to enhance the photothermal conversion effect, a foam skeleton layer with a micron-scale porous structure is formed. This helps the photothermal conversion layer to fully transfer moisture through its own capillary action, and at the same time facilitates the diffusion of steam outward through the pores, thereby improving the evaporation rate of the interface evaporator.
[0008] Preferably, the foam skeleton photothermal conversion layer uses foamed metal copper oxide as the photothermal layer substrate, which has excellent photothermal conversion effect and a pore density of 80~130 PPI. If the pore density is too low, it will reduce the diffusion rate within the water layer; if the pore density is too high, it will reduce the self-floating effect of the interface evaporator.
[0009] The water-transporting insulation layer of this invention improves capillary effect by constructing vertical through-holes in closed-cell foam and modifying the inner wall of the vertical holes and the upper and lower surfaces of the closed-cell foam with hydrogel. The water-transporting insulation layer consists of three layers: the upper and lower layers are hydrogel layers with millimeter-scale arrayed small pores, the middle layer is a closed-cell foam layer with millimeter-scale arrayed large pores, and the interior of the middle layer pores is a hydrogel hollow cylinder with arrayed small pores, forming an integral structure with the upper and lower hydrogel layers, thereby constructing vertical capillary water-transporting channels that run vertically through the layers, enabling water to be transported from bottom to top. The density of the capillary channels can be adjusted within a certain range. By matching the pore density with the photothermal conversion layer of the foam skeleton, the evaporation rate of the composite interface evaporator can be improved.
[0010] Preferably, the water supply insulation layer uses polymethacrylamide (PMI) closed-cell foam as the insulation material, with a thickness of 5-20 mm and a density of 20-60 kg / m³. 3The thermal conductivity is 0.02~0.06 W / m·K, the compressive strength is 0.2~3 MPa, the inner diameter of the vertically arranged channels in the PMI foam is 1.5~3 mm, the channel length is the same as the thickness of the closed-cell foam, and the pore density is 100~500 pores / m³. 2 This is beneficial for achieving good self-buoyancy and thermal insulation.
[0011] Preferably, the water-conducting insulation layer uses PVA hydrogel as the hydrophilic wall surface. The thickness of the upper and lower layers of PVA hydrogel is 0.5~3mm, and it has an array of millimeter-level vertical channels with an inner diameter of 0.5~1.5mm. The arrangement is the same as that of PMI closed-cell foam. The middle part is an array of hollow cylindrical PVA hydrogels with an inner diameter that is the same as that of the channels in the upper and lower PVA hydrogel layers. The above three parts are an integral structure, thereby forming a hydrophilic wall structure on the upper and lower surfaces and inside the channels of the closed-cell foam.
[0012] The present invention also provides a method for preparing a composite interface evaporator as described above, comprising the following steps: (1) A series of millimeter-level vertical channels are constructed inside the closed-cell foam by means of a pore-pressing mold, and the channels vertically penetrate the upper and lower surfaces of the foam.
[0013] Preferably, the closed-cell foam is PMI foam, which is hydrophobic, has a thickness of 5-20 mm, and a density of 20-60 kg / m³. 3 The thermal conductivity is 0.02~0.06 W / m·K, the compressive strength is 0.2~3 MPa, the vertical channel inner diameter is 1.5~3 mm, the channel length is the same as the thickness of the closed-cell foam, and the pore density is 100~500 pores / m³. 2 .
[0014] (2) Add the hydrogel monomer to deionized water and heat and stir with a magnetic stirrer until completely dissolved. Let the prepared aqueous solution stand at room temperature to remove bubbles and obtain a homogeneous and transparent solution.
[0015] Preferably, the hydrogel monomer is PVA powder with a degree of alcoholysis of 98-99% (mol / mol) and a degree of polymerization of 1700. The mass ratio of PVA powder to deionized water is 1:9, and the heating temperature is 95℃ to obtain a 10wt% PVA aqueous solution.
[0016] (3) Pour the prepared aqueous solution into a mold with an array of cylindrical structures. The cylindrical array is the same as that of the closed-cell foam pressing mold, and the outer diameter of the cylinder is smaller than the inner diameter of the closed-cell foam channel. Place the drilled closed-cell foam into the mold and press it to allow the aqueous solution to be poured from the bottom to the top of the closed-cell foam, thereby filling the upper and lower surfaces and interior of the foam with aqueous solution. Place the mold containing the aqueous solution and closed-cell foam in a freezer for a period of time, then take it out and thaw it. Use the cyclic freeze-thaw method to promote the gelation of the aqueous solution. After demolding, soak it in a certain concentration of NaCl aqueous solution to improve the structural stability of the water supply insulation layer, thereby obtaining the water supply insulation layer.
[0017] Preferably, the freezing temperature in the above-mentioned cyclic freeze-thaw process is -50~-20℃, the freezing time is 12~24h, the thawing time at room temperature is 3~6h, and the freeze-thaw cycle is 3~4 times.
[0018] Preferably, the concentration of the above-mentioned NaCl aqueous solution is 3.5~20wt%, and the soaking time is 0.5~2h.
[0019] (4) After silver is deposited on the surface of the foam metal oxide by magnetron sputtering and heat treatment is performed, silicon is then deposited on the surface to obtain a foam skeleton photothermal conversion layer containing a variety of photothermal conversion materials.
[0020] Preferably, the pore density of the foamed metal oxide is 80~130 PPI and the thickness is 1~5 mm.
[0021] Preferably, the sputtering power in the above magnetron sputtering silver plating process is 30~80W, the working gas pressure is 0.2~1Pa, the sputtering time is 5~30min, the annealing temperature is 200~300℃, and the annealing time is 0.5-3h.
[0022] Preferably, the sputtering power in the above magnetron sputtering silicon deposition process is 100~160W, the working gas pressure is 0.2~2Pa, and the sputtering time is 30~120min.
[0023] (5) The obtained foam skeleton photothermal conversion layer is immersed in 3.5~20wt% NaCl aqueous solution, and after taking it out, it is placed on the surface of the water supply insulation layer with the silver and silicon nanostructures facing upward, and assembled to form the composite interface evaporator.
[0024] This invention also provides the application of the above-mentioned composite interface evaporator in water evaporation and seawater desalination.
[0025] The composite interface evaporator proposed in this invention consists of two parts: a foam skeleton photothermal conversion layer and a hydrogel and closed-cell foam composite water supply and heat insulation layer. Compared with the prior art, it has the following advantages: (1) The foam skeleton photothermal conversion layer of the present invention has a variety of inorganic photothermal conversion materials, which can broaden the absorption range of the solar spectrum, enhance the light absorption and photothermal conversion performance, and thus increase the photothermal conversion temperature. In addition, the foam skeleton photothermal layer has a micron-level porous structure, which helps it to fully diffuse and transfer moisture by utilizing its own capillary action, while making it easy for the steam generated by the photothermal layer to diffuse outward through the pores, thereby improving the evaporation rate of the interface evaporator.
[0026] (2) The water conveying and heat insulation functions of the hydrogel and closed-cell foam composite water conveying and heat insulation layer of the present invention are separated. The closed-cell foam has a low thermal conductivity and is hydrophobic, which helps to reduce the heat loss from the photothermal layer to the water body and simultaneously achieve the self-floating of the interface evaporator. The hydrogel is used to modify the closed-cell foam to be hydrophilic, and the capillary effect is achieved through the array of vertical channels, which ensures that water can be continuously transported from bottom to top to the photothermal conversion layer. The vertical channels have low tortuosity, which can shorten the downward migration path of salt ions, making them circulate smoothly inside the interface evaporator and preventing the local salt ion concentration from being too high, thereby inhibiting salt crystallization on the evaporation surface. In addition, since the water conveying and heat insulation layer is perforated by a mold, the capillary water conveying rate can be flexibly controlled by adjusting the pore distribution density, thereby improving the evaporation rate.
[0027] (3) The hydrogel and closed-cell foam composite water supply and heat insulation layer of the present invention is prepared by the cyclic freeze-thaw method and then soaked in a certain concentration of NaCl aqueous solution. This not only improves the structural stability and mechanical properties of the hydrogel, but also increases the evaporation rate of the interface evaporator in salt water and enhances the salt resistance effect.
[0028] (4) The composite interface evaporator constructed by the present invention has an assembly structure, which is easy to replace. It provides a new method and new idea for the design and performance improvement of photothermal interface evaporators and has certain application prospects in the field of seawater desalination. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the process for preparing the hydrogel and foam skeleton material composite interface evaporator of the present invention. Figure 2 This is a schematic diagram of the mold structure used to prepare the hydrogel and closed-cell foam composite water-transporting and heat-insulating layer in Embodiment 1 of the present invention; Figure 3 This is a photograph of the water-conducting heat insulation layer prepared in Example 1 of the present invention; Figure 4 The figures show a physical image and a schematic diagram of the composite photothermal interface evaporator prepared in Embodiment 1 of the present invention; in the figures, 1 is the photothermal conversion layer of the foam skeleton; 2 is the top layer of hydrogel with arrayed vertical channels; 3 is the arrayed hollow cylindrical structure of hydrogel; 4 is the bottom layer of hydrogel with arrayed vertical channels; and 5 is the closed-cell foam with arrayed vertical channels. Figure 5 An optical micrograph of the photothermal conversion layer of the foam skeleton prepared in Example 1 of this invention; Figure 6 This is an electron micrograph of the photothermal conversion layer of the foam skeleton prepared in Example 1 of the present invention; Figure 7 The image shows the XRD test results of the photothermal conversion layer of the foam skeleton prepared in Example 1 of this invention. Figure 8 The image shows the contact angle test results of PMI closed-cell foam (a) and PVA hydrogel (b) in the water-conducting insulation layer prepared in Example 1 of this invention. Figure 9 The graphs show the evaporation rates of pure water under one solar radiation intensity in Embodiment 1 and Comparative Examples 1-5 of the present invention. Figure 10 The graphs show the results of the change rate of pure water mass over time under one solar radiation intensity in Embodiment 1 and Comparative Examples 1-5 of the present invention. Figure 11 This is a graph showing the evaporation rate of NaCl aqueous solutions of different concentrations under a single solar irradiance, as described in Example 1 of the present invention. Detailed Implementation
[0030] The technical solutions and implementation methods of the present invention will be described in detail below with reference to specific embodiments. Obviously, the embodiments described are only some embodiments of the present invention and are only used to help understand the present invention. They should not be regarded as specific limitations of the present invention.
[0031] Example 1
[0032] This embodiment provides an interfacial evaporator assembled from a foam skeleton photothermal conversion layer and a hydrogel and closed-cell foam composite water-transporting and heat-insulating layer, and its preparation method. The specific steps are as follows: (1) A copper foam with a size of 25×25×2mm and a pore density of 130PPI was placed in a muffle furnace for thermal oxidation treatment in an air atmosphere. The heating rate was 10K / min. The copper foam was heated from room temperature to 900℃ and then cooled to room temperature to obtain copper foam oxide.
[0033] (2) Place the above-mentioned foamed copper oxide into the magnetron sputtering chamber, and turn on the mechanical pump and molecular pump in sequence to evacuate the vacuum until the vacuum degree reaches 7.5 × 10⁻⁶. -3 Pa, the sputtering power was adjusted to 50W, the working gas pressure to 0.2Pa, the argon flow rate to 10ml / min, and the sputtering time to 5min. Silver was plated on the surface of the foamed copper oxide, and then annealed at 200℃ for 1h.
[0034] (3) Silicon is further deposited on the surface of the above-mentioned silver-plated foamed copper oxide, with a vacuum degree of 7.5 × 10⁻⁶.-3 The sputtering power was 150W, the working pressure was 0.2Pa, the argon flow rate was 10ml / min, and the sputtering time was 30min. Then the sputtering power and working pressure were adjusted to 100W and 2Pa respectively, and sputtering continued for 10min to prepare the above-mentioned foam skeleton photothermal conversion layer.
[0035] (4) PMI closed-cell foam is pressed and pores are created using a mold with an array of cylindrical structures. The PMI foam has a size of 25×25×10mm and a density of 50kg / m³. 3 With a thermal conductivity of 0.028 W / m·K and a compressive strength of 0.8 MPa, 25 vertical channels are constructed in a 5×5 matrix arrangement, with a diameter of 2 mm and a channel length of 10 mm.
[0036] (5) Add 10g of PVA particles with a degree of hydrolysis of 98% (mol / mol) and a degree of polymerization of 1700 to a beaker containing deionized water. The mass ratio of PVA particles to deionized water is 1:9. Heat the mixture to 95°C with a magnetic stirrer and stir continuously until the PVA particles are completely dissolved to obtain a 10wt% PVA aqueous solution. Let the obtained PVA aqueous solution stand at room temperature for 3h to remove bubbles and obtain a homogeneous and transparent solution.
[0037] (6) Pour the above 10wt% PVA solution into a mold with an array of cylindrical structures. The mold is assembled from a base plate and four side plates by mortise and tenon joints. The base plate has vertical cylinders arranged in a 5×5 matrix, which is the same as the array arrangement of the PMI foam pore-forming mold. The cylinder diameter is 1mm and the height is 13mm. The internal structure of the assembled mold is 25×25×13mm. Place the drilled PMI foam into the mold and press it to allow the PVA aqueous solution to be poured from the bottom of the PMI foam to the top. A 2mm and 1mm thick PVA aqueous solution layer is formed on the upper and lower surfaces of the PMI foam, respectively. Place the above mold containing PVA aqueous solution and closed-cell foam in a -50℃ freezer for 21h. Then take it out and thaw it at room temperature for 3h. Repeat this freeze-thaw cycle 3 times and then demold it. Then soak it in a 10wt% NaCl aqueous solution for 1h to obtain a water-conducting heat insulation layer.
[0038] (7) The foam skeleton photothermal conversion layer prepared above is immersed in a 10wt% NaCl aqueous solution for 10 min. After taking it out, it is placed on the surface of the water supply insulation layer with the silver and silicon nanostructures facing upward to obtain the composite interface evaporator.
[0039] The composite interface evaporator achieves a pure water evaporation rate of 2.28 kg / m³ under 2 hours of sunlight exposure at a given intensity. 2•h; When the NaCl aqueous solution concentration is 3.5wt%, 10wt%, and 20wt%, the brine evaporation rate of this composite interface evaporator after 2 hours of irradiation under one solar radiation intensity is 1.96 kg / m³. 2 ·h、2.09kg / m 2 ·h and 2.15kg / m 2 ·h.
[0040] Comparative Example 1
[0041] Copper oxide foam was prepared according to the method in Example 1.
[0042] The above-mentioned foamed copper oxide was immersed in pure water and subjected to an evaporation test under sunlight intensity. The evaporation rate after 2 hours of irradiation under pure water conditions was 0.81 kg / m³. 2 ·h.
[0043] Comparative Example 2
[0044] The foam skeleton photothermal conversion layer was prepared according to the method of Example 1.
[0045] When the foam skeleton photothermal conversion layer is immersed in pure water, the evaporation rate of the pure water after 2 hours of irradiation under a certain solar intensity is 0.85 kg / m³. 2 ·h.
[0046] Comparative Example 3
[0047] Copper oxide foam was prepared according to the method in Example 1. The copper oxide foam was then placed in a container with dimensions of 25×25×25 mm and a density of 34 kg / m³. 3 An interfacial evaporator was prepared on a melamine sponge.
[0048] The above-mentioned interfacial evaporator achieves a pure water evaporation rate of 1.74 kg / m³ under 2 hours of sunlight exposure. 2 ·h.
[0049] Comparative Example 4
[0050] Foamed copper oxide and a water-conducting insulation layer were prepared according to the method in Example 1. The foamed copper oxide was then placed on the water-conducting insulation layer to form an interfacial evaporator.
[0051] The interface evaporator achieves a pure water evaporation rate of 1.77 kg / m³ under 2 hours of sunlight exposure. 2 ·h.
[0052] Comparative Example 5
[0053] A foam skeleton photothermal conversion layer was prepared according to the method in Example 1. This foam skeleton photothermal conversion layer was then placed in a container with dimensions of 25×25×25mm and a density of 34kg / m³. 3An interfacial evaporator was prepared on a melamine sponge.
[0054] The interface evaporator achieves a pure water evaporation rate of 1.77 kg / m³ under 2 hours of sunlight exposure. 2 ·h.
[0055] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A hydrogel and foam skeleton material composite interface evaporator, characterized in that, The composite interface evaporator comprises two parts: a photothermal conversion layer and a water supply insulation layer. The photothermal conversion layer has a foam skeleton structure and is loaded with photothermal conversion material on its surface. The water supply insulation layer is an integral structure formed by hydrogel composite on the upper and lower surfaces and the inner surface of the vertical channels of a closed-cell foam with an array of millimeter-scale vertical channels. The water supply insulation layer has an array of millimeter-scale vertical capillary channels that penetrate the upper and lower surfaces. The method for preparing the water-conducting heat insulation layer specifically includes the following steps: S1. A millimeter-scale array of channels is constructed inside the closed-cell foam using a drilling mold with an arrayed cylindrical structure. The channels vertically penetrate the upper and lower surfaces of the closed-cell foam. S2. Pour the hydrogel monomer aqueous solution into a mold with an array of cylindrical structures. The cylindrical array is matched with the closed-cell foam channel array. The outer diameter of the cylinder is smaller than the inner diameter of the closed-cell foam channel. Place the drilled closed-cell foam into the mold and press it to make the hydrogel monomer aqueous solution pour from the bottom of the closed-cell foam to the top, filling the upper and lower surfaces of the closed-cell foam and the inner wall of the channel. S3. Place the mold containing the hydrogel monomer aqueous solution and closed-cell foam in a freezer at -50~-20℃ for 12~24h, then take it out and thaw at room temperature for 3~6h, repeat the freeze-thaw cycle 3~4 times, demold, and obtain the water-conducting heat insulation layer.
2. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The closed-cell foam has millimeter-scale vertical channels with an inner diameter of 1.5~3mm and a pore density of 100~500 pores / m³. 2 .
3. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The thickness of the hydrogel on the upper and lower surfaces of the closed-cell foam is 0.5~3mm, and the thickness of the hydrogel on the inner wall of the vertical pores of the closed-cell foam is 0.5~1.5mm.
4. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The closed-cell foam described in step S1 is hydrophobic, has a thickness of 5-20 mm, and a density of 20-60 kg / m³. 3 It has a thermal conductivity of 0.02~0.06 W / m·K and a compressive strength of 0.2~3 MPa.
5. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The photothermal conversion layer uses a metal oxide semiconductor with a foam skeleton structure as the substrate and a pore density of 80~130 PPI. A nanostructure containing silver and silicon is introduced by magnetron sputtering, and the resulting foam skeleton photothermal conversion layer has a micron-scale porous structure.
6. The hydrogel and foam skeleton material composite interface evaporator according to claim 5, characterized in that, The metal oxide semiconductor with a foam skeleton structure is foamed copper oxide with a pore density of 80~130 PPI.
7. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The method for preparing the photothermal conversion layer includes the following steps: silver is deposited on the surface of the foam metal oxide by magnetron sputtering, followed by heat treatment, and silicon is deposited on its surface to obtain the foam skeleton photothermal conversion layer.
8. The hydrogel and foam skeleton material composite interface evaporator according to claim 1, characterized in that, The photothermal conversion layer and the water supply insulation layer were respectively immersed in a 3.5~20wt% NaCl aqueous solution for 0.5~2h. Then the photothermal conversion layer was assembled on the surface of the water supply insulation layer to obtain a composite interface evaporator.
9. The application of the composite interface evaporator according to any one of claims 1-8 in water evaporation and seawater desalination.
Citation Information
Patent Citations
Preparation method of compound photo-thermal interface evaporator
CN117585750A
Preparation method of double-layer polypyrrole deposition foam nickel sodium alginate hydrogel solar evaporator
CN119191429A